The Influence of the K3 Program and Incentives on Employee Productivity Mediated by Job Satisfaction in Millennial Generation Employees in Bekasi District - Rustianah, Rustianah; Ardianto, Riski Eko; Hasyim, Wachid (Formosa Journal of Multidisciplinary Research, 2024)
This study discusses the effect of the K3 (Occupational Health and Safety) program and incentive on employee productivity mediated by job satisfaction in millennial generation employees in Bekasi Regency. This study uses a quantitative approach with a sample size of 96 samples. Sample calculation using the Lemeshow formula.  The results are Occupational health and safety (OHS) programs have no positive impact on the productivity, incentive has a significant influence on the productivity, Job satisfaction has a direct impact on the productivity, Occupational health and safety (OHS) programs play an important role in improving job satisfaction, incentive plays an important role in increasing the job, Occupational health and safety (OHS) programs can influence the productivity through the mediation of job satisfaction and incentive plays an important role in increasing the productivity mediated by their level of job satisfaction.